Bernie Rouzes and Ron Felix perform songs on violin and guitar - Thomas, Gerald (1971)
Bernie Rouzes et Ron Felix jouent de la musique et font la conversation avec les gens dans un bar. -- Bernie Rouzes and Ron Felix play and chat with people in a busy bar. Transcription du F1661/C2292/CD-F0978 -- Transcript of F1661/C2292/CD-F0978